PENGELOLAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MISKIN PERKOTAAN (PNPM-MP) DALAM RANGKA PENANGGULANGAN KEMISKINAN DI KECAMATAN NANGGALO - Dartanto , (Jurnal Bahana Manajemen Pendidikan, 2014)
This research is motivated by PNPM-Mandiri Perkotaan project who has the weakness management in district Nanggalo.  The purpose of this study to get informations about: (1) The planning of PNPM Mandiri Perkotaan project to effort the poor community empowerment in district Nanggalo, (2) The implementation of PNPM Mandiri Perkotaan project to effort the poor community empowerment, and (3) The controlling and evaluation of PNPM Mandiri perkotaan project to effort the poor community empowerment. The research methode is used descriptive form, the population of the study is all the managers of PNPM Mandiri Perkotaan in district Nanggalo which amounts 29 people. Instrument research using questionnaire with a Likert scale models. As for testing the validity of the instrument by using the formula product moment Pearson, and reability test performed by the instrument internal consistency by using Cronbach Alpha. Test results are valid and reliable questionnaire. The datas were processed using the formula data. The result of the study showed that management of PNPM Mandiri Perkotaan project in district Nanggalo in planning, implementation and controlling and evaluation is in the well category, with average score of 3,95. Kata kunci : Pengelolaan PNPM Mandiri Perkotaan